2016
DOI: 10.1111/ijcp.12874
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical activity in early adulthood and middle-age on bone health after menopause in epidemiological population from Silesia Osteo Active Study

Abstract: SummaryBackground: Osteoporosis is a growing problem in women after menopause. Among factors protecting from this disease is a physical activity (PA). Aim:The objective of the study was to evaluate the influence of PA in early adulthood and at middle-age on bone health after menopause. Material and Methods:The study group consisted of 362 randomly recruited postmenopausal women after menopause. Mean age was 65.2±6.9 years. Medical history was collected from all participants, and they completed questionnaires a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A previous study confirmed that QUS measurements at the calcaneus might provide information comparable to DXA examinations at the femoral neck and lumbar spine in post-menopausal women [105]. Several papers recommend PA as the preventive modality of lifestyle [30,43,106,107]. Current osteopenia treatment guidelines include optimal exercise regimens for attenuating BMD loss, and improving poor balance and muscle strength to address other fracture-related risk factors.…”
Section: Resultsmentioning
confidence: 86%
“…A previous study confirmed that QUS measurements at the calcaneus might provide information comparable to DXA examinations at the femoral neck and lumbar spine in post-menopausal women [105]. Several papers recommend PA as the preventive modality of lifestyle [30,43,106,107]. Current osteopenia treatment guidelines include optimal exercise regimens for attenuating BMD loss, and improving poor balance and muscle strength to address other fracture-related risk factors.…”
Section: Resultsmentioning
confidence: 86%
“…Their current physical capacity was measured, their bone density was measured with ultra sounds and DXA was performed on lumbar vertebrae. The results suggest that current physical capacity has significant influence on BMD, but physical activity in youth has no impact on it [21].…”
Section: Training In Youth and Fractures In Old Agementioning
confidence: 83%
“…The research was a part of the Silesia Osteo Active Study, which was conducted in 2015. 26,29,30 A detailed description of the Ca, Zn, Cu, P, and pH assessment methods was published in our previous work. 26 The study obtained the approval from the Ethics Committee at the Medical University of Silesia (approval No.…”
Section: Methodsmentioning
confidence: 99%